Construction of a short circuit frequency map to define GMAW-S parameters during WPSs development (2018)
A short circuit frequency map was constructed for GMAW-S using a carbon steel filler metal class AWS ER70S-6 and 75%Ar-25%CO2 shielding gas. This kind of map is proposed as a tool for selecting GMAW-S currents and voltages that enable welds with higher stability and quality. The map was constructed by analyzing current and voltage signals recorded during welding applications at 5000 samples/second. Adequate operation regions were defined over the map based on visual inspection results of bead-on-plate welds and the establishment of instability boundaries. Some examples were analyzed by locating two common parameters for industrial welding qualification (current and voltage) and drawing the limits established by AWS D1.1:2015 code for these essential variables (±7% PQR voltage and ±10% PQR amperage) on the frequency map. The results show that sometimes these limits may contain regions with poor stability related to electrode stubbing against the base metal and lack of arc re-ignition.